2016
DOI: 10.1155/2016/2926436
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cells and Their Multiple Roles during Malaria Infection

Abstract: Dendritic cells (DCs) play a central role in the initiation of adaptive immune responses, efficiently presenting antigens to T cells. This ability relies on the presence of numerous surface and intracellular receptors capable of sensing microbial components as well as inflammation and on a very efficient machinery for antigen presentation. In this way, DCs sense the presence of a myriad of pathogens, including Plasmodium spp., the causative agent of malaria. Despite many efforts to control this infection, mala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 125 publications
0
24
0
2
Order By: Relevance
“…Our observation that T. cruzi infection stimulated the release of TNF-α, IL-1β, IL-6, IL-8, IL-10 (involved in the control of intracellular infection) are in contrast with previous report showing no increase in the basal production of cytokines by human DCs infected with T. cruzi (Van Overtvelt et al, 1999 ). However, this effect presents similarity to infection by other pathogens, which induce DCs activation (Henderson et al, 1997 ; Gorak et al, 1998 ; Yamamoto et al, 1998 ; Amorim et al, 2016 ).…”
Section: Discussionmentioning
confidence: 96%
“…Our observation that T. cruzi infection stimulated the release of TNF-α, IL-1β, IL-6, IL-8, IL-10 (involved in the control of intracellular infection) are in contrast with previous report showing no increase in the basal production of cytokines by human DCs infected with T. cruzi (Van Overtvelt et al, 1999 ). However, this effect presents similarity to infection by other pathogens, which induce DCs activation (Henderson et al, 1997 ; Gorak et al, 1998 ; Yamamoto et al, 1998 ; Amorim et al, 2016 ).…”
Section: Discussionmentioning
confidence: 96%
“…Elegant studies on the mechanism of antigen-specific T cell stimulation by peptide-bearing exosomes demonstrated activation of T cell proliferation mainly in the presence of mature dendritic cells 44 . We thus used a functional assay 38 to demonstrate the potential capacity of HuRex to interact with dendritic cells as they play a pivotal role in antigen presentation in natural malarial human infections 45 . This assay previously demonstrated that ganglioside-containing vesicles such as viral-like particles or exosomes could be captured by mature dendritic cells expressing Siglec-1 39 .…”
Section: Discussionmentioning
confidence: 99%
“…The infectious status of sporozoites might influence the innate immune cells that ultimately modulate the CD8 + T cell response. Dendritic cells (DCs) are shown to be involved in the induction of protective immunity against various pathogens including Plasmodia ( 22 , 23 ). Only limited studies demonstrated that the role of distinct subsets of DCs in the generation of malaria protective CD8 + T cells ( 22 ) including LS-specific CD8 + T cells, known to confer the sterile immunity evoked by RAS immunization ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dendritic cells (DCs) are shown to be involved in the induction of protective immunity against various pathogens including Plasmodia ( 22 , 23 ). Only limited studies demonstrated that the role of distinct subsets of DCs in the generation of malaria protective CD8 + T cells ( 22 ) including LS-specific CD8 + T cells, known to confer the sterile immunity evoked by RAS immunization ( 22 ). While depletion of DCs fails to induce protection induced by RAS vaccination, adoptive transfer of DCs loaded with circumsporozoite protein (CSP) antigen is shown to generate antigen-specific CD8 + T cells conferring partial protection on the challenge with Inf.…”
Section: Introductionmentioning
confidence: 99%